PENGARUH MOTIVASI BELAJAR AL-QUR’AN TERHADAP PRESTASI BELAJAR AQIDAH AKHLAQ SANTRI PUTRI KELAS VIII D PONDOK PESANTREN TAHFIDZUL QUR’AN ABI UMMI AMPEL BOYOLALI TAHUN PELAJARAN 2024/2025 - Kirstyaustin, Jhil Alesia; Hidayah, Nur (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to analyze the influence of Qur’an learning motivation on Aqidah Akhlaq learning achievement among female students of Grade VIII D at the Junior High School of Tahfidzul Qur’an Abi Ummi Islamic Boarding School, Ampel Boyolali, in the 2024/2025 academic year. The study employed a descriptive quantitative approach with a correlational design. Data were collected through a Qur’an learning motivation questionnaire and documentation of Aqidah Akhlaq academic scores. The data were analyzed using descriptive statistics, Pearson Product Moment correlation, and simple regression assisted by SPSS version 26.0. The results indicate that students’ Qur’an learning motivation is categorized as high, with an average score above 80. The learning achievement in Aqidah Akhlaq is also classified as good, with an average score of 87. The correlation analysis shows a coefficient (r) of 0.67 and a significance value (p) of 0.001 (<0.05), indicating a strong and significant positive relationship between Qur’an learning motivation and Aqidah Akhlaq achievement. The regression analysis further reveals that learning motivation contributes 45% to the variance of Aqidah Akhlaq achievement. The study implies that Qur’an-based spiritual motivation is a key determinant of both academic performance and moral development. Therefore, Islamic boarding schools should integrate Qur’an memorization programs with Aqidah Akhlaq learning based on Qur’anic values.